2019
DOI: 10.1007/s42452-019-0762-3
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of metal-tolerant and antibiotic-resistant bacteria from soil samples of Cachar district of Assam, India

Abstract: The present study aims to assess the physicochemical properties and prevalence of microbial communities in soils samples collected from different locations of Cachar district, Assam, India. Bacterial communities in the soil were screened by morphological, biochemical and 16S rDNA sequence analysis and were identified as Bacillus megaterium, Bacillus cereus, Pseudomonas aeruginosa and Chromobacterium pseudoviolaceum. High concentrations of toxic metals negatively affect bacterial growth, and therefore, the mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 35 publications
4
21
1
1
Order By: Relevance
“…Heavy metals are natural elements with atomic number greater than 20, characterized by a relatively high density (at least 5 g cm −3 ), and are toxic even at low concentrations [1][2][3]. They are characteristically existing components found in changing variation in the environments and are part of human daily activities, they are also found in important structures and in a range of other artificial mixes [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heavy metals are natural elements with atomic number greater than 20, characterized by a relatively high density (at least 5 g cm −3 ), and are toxic even at low concentrations [1][2][3]. They are characteristically existing components found in changing variation in the environments and are part of human daily activities, they are also found in important structures and in a range of other artificial mixes [4].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the fact that they are non-biodegradable, they may also undergo microbial or chemical transformation [8,9,11,12]. Recently, Hasani et al [13] and Nath et al [3] reported that heavy metal polluted environments activate co-selection process and cause a decrease in microbial tolerance to antibiotics due to their ability to co-regulate genes responsible for antibiotic resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The physical linkage of antibiotic resistance and metal resistance is encoded on the plasmid that confers resistance to the bacteria even when only one co-selecting agent (either antibiotics or heavy metals) is present [ 78 80 ]. Co-selection of antibiotic resistance and heavy metal tolerance by P. aeruginosa is well documented in many studies [ 81 , 82 , 41 , 83 ]. Bacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…The initial concentration of these metal salts in nutrient plates was 100 μg/mL, and bacterial growth was observed by streaking on respective plates. Metal concentration was progressively increased by 50–100 μg/mL on a fresh agar plate, and the minimum inhibitory concentration (MIC) was noted when the isolates failed to grow on respective plates [ 41 ]. The experiment was conducted separately for Cd, Cu, Fe, Pb and Zn taking five replicates at each concentration.…”
Section: Methodsmentioning
confidence: 99%
“…During the biogeochemical cycle of As a huge number of microbes are involved. There are various types of mechanism are occurred such as redox reaction, methylation, precipitation, biosorption by cell biomass, entrapments through cellular capsule and production of induced proteins, active cell transport, in the bacteria, fungi, algae, mosses, higher plants and macrophytes for the removal or mitigation of heavy metals including As [7,23,27,35,38].…”
Section: Discussionmentioning
confidence: 99%